PERTANGGUNGJAWABAN POLITIK PRESIDEN PASCA AMANDEMEN UUD 1945 - -, Hendra (JWP (Jurnal Wacana Politik), 2016)
After the UUD 1945 amendment, there is fundamental change in the Indonesian governmental system. This changes well-marked with the facts that after amandement there is an alteration to the patern of president or vice president election, and the regulation of the relation between president and DPR. This changes has influence the president political responsibility after amandement.